PENGARUH STRUKTUR DAN MEKANISME CORPORATE GOVERNANCE PADA TINGKAT KEPATUHAN MANDATORY DISCLOSURE KONVERGENSI IFRS - Widjayanti, Septri Ari; Wahidawati, Wahidawati (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2015)
The purpose of this research is to test and to analyze whether the mechanism and the structure of corporate governance has an influence to the level of compliance of IFRS convergence mandatory disclosure on manufacturing companies which are listed in Indonesia Stock Exchange (IDX) from 2011 to 2013 periods. The samples are 84 manufacturing companies and the characteristic of sample selection has been done by using purposive sampling method. The data analysis has been carried out by using multiple linear regressions analysis. The result of the research describes thatthe proportion of female commissioner, managerial ownership, institutional ownership, the number of the meeting of audit committee, and the proportion of independent commissionerhave influence to the level of compliance of the IFRS convergence mandatory disclosure whereas theeducation background of the Main Commissioner, the number of the audit committee and the number of meeting of the board of commissionerdoes not have any significant influence to the level of compliance of the IFRS convergence mandatory disclosure.Keywords: The Structure of Corporate Governance, the Mechanism of Corporate Governance, the Level of Compliance of the IFRS convergence mandatory disclosure.